Aligned MoOx/MoS2 Core–Shell Nanotubular Structures with a High Density of Reactive Sites Based on Self‐Ordered Anodic Molybdenum Oxide Nanotubes. (7th September 2016) - Jin, Bowen; Zhou, Xuemei; Huang, Li; Licklederer, Markus; Yang, Min; Schmuki, Patrik
Abstract: The present work demonstrates the self‐organized formation of anodic molybdenum oxide nanotube arrays. The amorphous tubes can be crystallized to MoO2 or MoO3 and be converted fully or partially into molybdenum sulfide. Vertically aligned MoO x /MoS2 nanotubes can be formed when, under optimized conditions, defined MoS2 sheets form in a layer by layer arrangement that provide a high density of reactive stacking misalignments (defects). These core–shell nanotube arrays consist of a conductive suboxide core and a functional high defect density MoS2 coating. Such structures are highly promising for applications in electrocatalysis (hydrogen evolution) or ion insertion devices.